Design, Construction, and Testing of an Experimental Apparatus for Single Optical Pyrometer-Based High- Temperature Differential Thermal Analysis for the Study of Rare Earth Material Properties. - Andrews, Tyler C. (Tufts Archival Research Center, 2005)
In this report, a new system for high-temperature, optical-pyrometry-based, differential thermal analysis (DTA) is presented to be used with a previously designed ultra-high temperature induction reactor. Numerical thermal analysis was performed using ANSYS Icepak and COMSOL Multi-physics software. A numerical correlation was established between the heating rate of the reactor and the temperature difference between the reactor and a sample of alumina or silica; this correlation was of the form dT = A e b*T, where A and b are constants determined by the heating rate. A second correlation was found between the maximum temperature difference, dTmax, between samples of silica and alumina and the sample to sample-cup mass ratio, MR, following the function dTmax = 0.0438 MR 2.4073. A third constant correlation was found between heat of fusion, Hf, and integrated area under a melt-plateau curve, A, as a function Hf =0.2983A.Two physical tests were performed in addition to the thermal analyses described above. In one test, the functionality of a pyrometer-sight designed to focus incoming radiation from four specific areas was found to be effective by showing clear spacing between four readings. In a second test, a thermocouple-based high-temperature differential thermal analysis was performed. Due to significant and inconsistent errors produced by the coupling of induction field and the thermocouple wire, it is recommended that thermocouples not be used in induction-heated apparatuses for high-temperature DTA in the future.